2017
DOI: 10.1080/17453674.2017.1377017
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic incidence and hip disorders

Abstract: Background and purposeThe role of pelvic incidence in hip disorders is unclear. Therefore, we undertook a literature review to evaluate the evidence on that role.MethodsA search was carried out on MEDLINE, SCOPUS, CENTRAL, and CINAHL databases. Quantitative analysis was based on comparison with a reference population of asymptomatic subjects.ResultsThe search resulted in 326 records: 15 studies were analyzed qualitatively and 13 quantitatively. The estimates of pelvic incidence varied more than 10 degrees from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…No differences in symptom duration, sex, or BMI were found between the two groups (Table 4). When all of the participants were divided into two groups (pelvic incidence > 55°, pelvic incidence < 55°) based on earlier studies [18,38,41], pelvic incidence greater than 55° had a sensitivity of 45.4%, specificity of 86.7%, positive predictive value of 86.3%, and negative predictive value of 71.3% for predicting acetabular labral tears in all of the patients (Table 5). In patients without FAI, pelvic incidence greater than 55° had a sensitivity of 59.8%, specificity of 87.5%, positive predictive value of 84.5%, and negative predictive value of 65.6% for predicting acetabular labral tears (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…No differences in symptom duration, sex, or BMI were found between the two groups (Table 4). When all of the participants were divided into two groups (pelvic incidence > 55°, pelvic incidence < 55°) based on earlier studies [18,38,41], pelvic incidence greater than 55° had a sensitivity of 45.4%, specificity of 86.7%, positive predictive value of 86.3%, and negative predictive value of 71.3% for predicting acetabular labral tears in all of the patients (Table 5). In patients without FAI, pelvic incidence greater than 55° had a sensitivity of 59.8%, specificity of 87.5%, positive predictive value of 84.5%, and negative predictive value of 65.6% for predicting acetabular labral tears (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Observou-se também em estudos de imagem que baixa incidência pélvica (definida como o ângulo entre uma linha perpendicular ao ponto central do platô sacral e uma linha a partir deste ponto até o centro axial das cabeças femorais 16 ) ( Fig. 1 ), ou seja, maior inclinação anterior da pelve pode estar associada ao IFA de tipo misto, 17 à rotação pélvica, à fase de apoio, ao movimento dos membros superiores, e ao ângulo de progressão do pé (APP), o qual é normalmente cerca de 7° em direção lateral. 18 Retroversão femoral proximal e limitação da rotação medial são vistos frequentemente em pacientes com IFA, podendo levar a um APP em rotação lateral excessiva.…”
Section: Exame Físicounclassified
“…Imaging studies also revealed that low pelvic views (defined as the angle between a line perpendicular to the central point of the sacral plateau and a line from this point to the axial center of the femoral heads) 16 ( Fig. 1 ), that is, a greater pelvic anterior inclination, may be associated with mixed-type FAI, 17 pelvic rotation, stance phase, upper limb movement and foot progression angle (FPA), which is usually about 7° in the lateral direction. 18 Proximal femoral retroversion and medial rotation limitation are frequently seen in FAI patients, and may lead to an excessive FPA in lateral rotation.…”
Section: Introductionmentioning
confidence: 99%
“…143 Relationship of sagittal balance and hip disorders is currently controversial. 151 PI is an indicator of acetabular retroversion, 152 and patients with a higher PI have more anteriorly positioned femoral heads and a better ability to compensate for sagittal imbalance with pelvic retroversion. 150 Sagittal rotation also changes the socket orientation of the acetabulum, contributing to or protecting from FAI: The L-CEA and percentage of acetabular crossover increases with pelvic forward tilt and decreases with back tilt.…”
Section: Thresholdsmentioning
confidence: 99%
“…In fact, decreasing values of SS may allow greater impingement-free hip flexion by effectively reducing femoral coverage anteriorly. Saltychev et al, 151 however, challenged this relationship as not showing evidence of a substantial role of pelvic incidence in hip Angle between the line perpendicular to the sacral plate at its midpoint and a line from the midpoint between the axis of the two femoral heads to the center of the surface of the sacrum PI ¼ SS þ PT Imaging Methodology for Hip Preservation Mascarenhas et al 221 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Thresholdsmentioning
confidence: 99%